Origin country conflict and immigrant physical health - Ryan A. Compton; Andrea N. Craig; Dörte Heger; Karl Skogstad (RWI - Leibniz-Institut für Wirtschaftsforschung, 2024)
Using multiple waves of Statistics Canada's Canadian Community Health Survey (CCHS) linked with the Longitudinal Immigration Database (IMDB), as well as the Uppsala Conflict Data Program (UCDP)/ International Peace Research Institute in Oslo (PRIO) Armed Conflict Dataset, we examine the effect of exposure to pre-migration conflict on the post-migration physical health outcomes of immigrants to Canada. Our results demonstrate that immigrants from conflict zones face unique physical health challenges that continue post-migration. Better understanding these challenges will help health policy makers and providers to better respond to the needs of people migrating from these regions of the world. – – Wir kombinieren Daten des Canadian Community Health Survey (CCHS) von Statistics Canada mit der Longitudinal Immigration Database (IMDB) sowie dem Armed Conflict Dataset des Uppsala Conflict Data Program (UCDP)/International Peace Research Institute in Oslo (PRIO), um die Auswirkung gewaltsamer Konflikte vor der Migration auf die körperliche Gesundheit von Einwanderinnen und Einwanderern nach Kanada zu untersuchen. Unsere Ergebnisse zeigen, dass Einwanderinnen und Einwanderer aus Konfliktgebieten verstärkt gesundheitliche Probleme haben, die auch nach der Migration bestehen bleiben. Ein besseres Verständnis dieses Zusammenhangs ermöglicht es Gesundheitspolitikern und -anbietern, besser auf die Bedürfnisse von Menschen zu reagieren, die aus Konfliktregionen migrieren.
Keywords: I10; J15; D74; 330; Conflict; health; refugees; immigrants; Canada